(untitled) (Cadernos de Sociomuseologia, 2009)
In the last few years, reflections around knowledge building in the museology area have increased considerably, allowing us to cast many gazes over our actions, and, consequently, enabling us to a wider debate around our professional action field, decreasing our exclusion from the academic environment – museologists reproducing the knowledge produced in other areas. In the present work, we shall approach some issues related to the museological process, taking as a reference several studies about the subject, which, due to the time given to us in this round table, could not be re-presented here for discussion. Besides, we have dedicated a chapter to such approach in our publication titled “Museological Process and Education: building a didactic-community museum”. So we have opted instead to carry out a reflection about exclusion, looking into the museum institution and into the application of museological processes; in other words, we shall carry out a self-criticism, in which I include myself, affecting an analysis that will be debated here, considering, additionally, that the museums and museological practices are in relation to the other social global practices, therefore, they are the result of human relations at each historical moment. Finally, based on our lived experience, we shall give continuity to our reflection process, highlighting the importance of knowledge production for the area of museology and the relevance of the theory-practice relation, punctuating some aspects we think that may contribute to the construction of a museological action that may serve as a historical elaboration in securing a space for self- determination.